Application Of Pbm-Nir Therapy For Postpartum Mother's Discomfort In Maternity Nursing Care - Dian Nabillah, Hasna; Rosnani; Dia Cahya Wati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Normal post partum is post partum discomfort due to uterine involution. Uterine involution in patients can cause pain in the uterus called afterpains. Discomfort caused by uterine involution requires various treatments to minimize the pain felt by the mother so that the mother's comfort can return. This can be overcome with non-pharmacological pain management strategies through innovative near infrared phototherapy or near infrared photobiomodulation (PBM NIR). The aim of this research is to analyze the results of implementing pain management with non-pharmacological PBM NIR therapy in normal post-partum mothers with post-partum discomfort nursing problems. Case study that focuses on the implementation of non-pharmacological nursing pain management techniques with PBM NIR therapy. The case study subjects were 3 normal post-partum maternal patients with the same problem, namely post-partum discomfort in the obstetrics room at the Muhammadiyah Hospital in Palembang. The results of the study showed that the implementation of non-pharmacological pain management techniques with PBM NIR therapy had an effective effect on dealing with post-partum discomfort with complaints of decreased discomfort, decreased moaning, and strong uterine contractions. Implementation of pain management can improve the comfort status of normal postpartum mothers. This study makes an important contribution to understanding of the role of nonpharmacological techniques in postpartum pain management, as well as highlighting the importance of implementing innovative therapies for labor, as well as highlighting the importance of implementing innovative therapies to improve the quality of care in postpartum mothers.